Analisis Komparatif Pendapatan dan Efisiensi Usahatani Padi Sawah Dengan Usahatani Padi Gogo di Kabupaten Konawe Selatan - Erna, Erna; Taridala, Sitti Aida Adha; Indarsyih, Yusna (Department of Agribusiness, Halu Oleo University, 2018)
The research was backed by extensive growth differences by production, harvesting, and productivity at the level of Southeast Sulawesi Province and South Konawe Regency. Data at the provincial level indicate that wetland paddy has increased harvested area, production, and productivity, whereas dryland paddy has decreased harvested area, production, and productivity. In addition, there is a difference in the practice of cultivation, the technology and the prices of products between wetland paddy and dryland paddy. This research aims to analyze the difference of income and efficiency among wetland paddy farming in Cialam Jaya Village Konda Sub-district with dryland paddy farming in Wolasi Village Wolasi Sub-district. The determination of the research area is done purposively on the considerations of the largest of wetlands and harvest area of dryland paddy in each sub-district of producers. The research from December 2016 until July 2017. The Total of wetland paddy farmers as many as 56 respondents and dryland paddy farmers as many as 13 respondents. Data analysis used analyses of income, R-C ratio and different test (independent samples t-test). The results of the research showed that the wetland paddy farming income amount Rp 9.743.521/Ha/MT and the efficiency value from revenue to cost 3,00, while the income of dryland paddy farming amount Rp 4.989.634/Ha/MT and the efficiency value from revenue to cost 1,66. The results of the analysis of the different test (independent samples t-test) showed that there is no significant income disparity between wetland paddy farming with dryland paddy farming, whereas for efficiency, there is a significant efficiency disparity between wetland paddy farming with dryland paddy farming. The income and efficiency of wetland paddy farming is bigger than dryland paddy farming. The author suggests to Local Government of South Konawe Regency in order to increase production to achieve food self-sufficiency, it is necessary done intensive outreach to farmers about the use of organic fertilizers and organic pesticides to maintain the sustainability of land and suppress the production costs.